German and Italian activities in Northern Spain (report)
012b-0045-002 Sir Walter Confidential GERMAN AND ITALIAN ACTIVITIES IN NORTHERN SPAIN The following information regarding recent German and Italian activities in the Basque Country has been received by the Basque Government from reliable sources. Concentration of Troops The bicycle factory of LOINAZ, at ALZA, near PASAJES (GUIPUZCOA) has been converted into a barracks for a military engineer unit. On the 9th instant, the warehouses of the port of PASAJES were fitted up as barracks, in which engineers who were lately at SAN SEBASTIAN have been quartered. These soldiers belong to the 1927 recruiting class and their transfer seems to be a part of a wider plan of concentration, according to which further troop concentrations have taken place at several points near the Pyrenees. On April 14, a battalion of 800 men reached the town of ELIZONDO (NAVARRA) and were later distributed in villages in the Valley of BAZTAN, of which ELIZONDO is the chief town. They were reinforcements for the 334th Battalion already quartered there. On the same date a further 800 men came to strengthen the garrison at VERA. Fourteen lorries with soldiers arrived at BURGUETE from PAMPLONA, where large concentrations of troops have taken place. ELIZONDO, VERA and BURGUETE are on the Spanish French frontier line. There are no barracks in these towns, which have not previously been garrisoned. At VITORIA (ALAVA) orders have been given to arrange for the billeting of the 52nd Division, which is expected any day. The aerodrome at VITORIA, which is at the service of the German airlines, is 80 miles from the frontier. In accordance with plans to reinforce the coast and frontier with military garrisons, various battalions have arrived at BILBAO (VIZCAYA) from Central and Eastern Spain. 292/946/12b/45(ii)